Pemenuhan Hak Masyarakat Atas Pencetakan Kartu Tanda Penduduk Elektronik di Kota Ambon - Tomasila, Sindi Marlen; Saptenno, Marthinus Johanes; Holle, Eric Stenly (Jurnal Saniri, 2022)
Introduction: Good public service is the right and hope of every citizen and resident. Especially to apply the concept of good governance in Indonesia, one of the strategic choices is through the implementation of public services in order to form good governance. However, in its implementation there are still public services that are not in accordance with public service standards so that it has implications for the occurrence of maladministration actions that can cause harm to the community. One of them is the uncertainty of time in the service process.Purposes of the Research:  The purpose of writing this thesis is to find out and analyze the 30 (thirty) minute period of service standards for making Electronic Identity Cards (e-KTP) that are not met, categorized as maladministration and legal remedies if the time period according to the service standards is not met.Methods of the Research: The type of research used in this research is normative legal research, namely legal research conducted by examining library materials or secondary materials consisting of primary legal materials and secondary legal materials. These materials are arranged systematically, studied, then a conclusion is drawn in relation to the problem under study.Results / Findings / Novelty of the Research: The results and discussion show that the 30 (thirty) minute period of completion of the e-KTP printing service at the Ambon City Population and Civil Registration Office in 2019 to early 2022 was not carried out in accordance with the contents of service standards with the constraints of limited e-KTP printing machines, the lack of officers in the e-KTP printing section and the lack of e-KTP forms per day which are not proportional to the number of people who will print e-KTPs, resulting in time uncertainty and work delays which have an impact on service discrimination. to get fast service. This action certainly deviates from administrative ethics which is referred to as maladministration. Seeing this, the construction of legal liability for maladministration acts carried out by public service providers needs to be reviewed, because the sanctions imposed have not been able to prevent maladministration actions that occur.